MULTIPLE DEEP NECK SPACE ABSCESSES OF ODONTOGENIC ORIGIN IN AN ELDERLY PATIENT: A CASE REPORT - Muhammad Destrian Cossandra; Wifaqi Oktaria; Meilina Wardhani; Taufik Hidayat; Melani Jalali; Lilis Khairani; Ahmad Ghiffari; Liza Chairani (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Deep neck space abscess are serious bacterial infections involving cervical fascial spaces and may lead to life-threatening complications. Recent evidence suggests that, despite antibiotic availability, the incidence of these infections remains significant and may be increasing, particularly due to odontogenic sources. We report a case of a 65-year-old male presenting with progressive neck swelling originating from untreated dental infection. Clinical examination and contrast-enhanced CT scan revealed multiple deep neck space infections involving bilateral submandibular, submental, left parapharyngeal, and supraclavicular spaces. Laboratory findings showed leukocytosis and hypoalbuminemia. The patient was managed with broad-spectrum intravenous antibiotics and surgical drainage. Odontogenic infection remains the leading cause of deep neck space abscess in adults. Multispace involvement is associated with higher risk of complications, including airway obstruction, sepsis, and mediastinitis. Notably, elderly patients may present with minimal systemic symptoms despite extensive infection, highlighting the importance of imaging. Epidemiological data from global and Indonesian studies indicate that deep neck space abscess continue to occur frequently, with odontogenic infections as the primary source. Multiple deep neck space abscess can present insidiously in elderly patients. Early diagnosis using CT imaging and prompt management with antibiotics and surgical drainage are essential. Prevention should focus on improving oral hygiene and controlling underlying comorbidities.